Pengabdian Masyarakat Berbasis Kearifan Lokal (Local Wisdom) Permainan Tradisional Geo Masyarakat Bima - Irfan, Irfan; Nasrullah, Nasrullah (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Geo games are traditional games of the Bima community as part of the culture, played by the Bima community in the past, which were carried out by the ancestors of the Bima community. The objectives of implementing this community service are: 1) The community preserves the local wisdom of the traditional geo games of the Bima community, and 2) The community receives benefits from various community service activities based on the local wisdom of the traditional geo games of the Bima community. The method of socialization and performance of traditional geo games, the time and place of this community service were carried out in October 2025, at the activities at MIN 1 Bima. The results and discussion of traditional geo games are folk games of the Bima community that need to be preserved through various integrated activities by the government, universities, and the community. This aims to explore the potential of culture and traditional sports games that are instilled in students. Instilling cultural values ​​​​in the world of education is one of the effective points for the formation of sustainable character for the next generation as an effort to preserve them in the school environment. Conclusion: 1) Able to preserve culture so that the younger generation knows more deeply about the culture of traditional geo games. 2) Able to develop social values, togetherness, and form physical and mental skills in traditional geo games. 3) Able to manage strategically, skill, spirit, and never give up. 4) Traditional geo games allow the players to reminisce with the ancestral game culture that continues to be carried out as an effort to maintain the integrity of culture in the next generation